LANGUAGE AND THE COMMUNICABILITY OF RECEIVED WISDOMS: AN INTERVIEW WITH CHARLES BRIGGS - Silva, Daniel do Nascimento e (Revista da Anpoll, 2016)
Charles Briggs was interviewed in his visit to Brazil, where he taught in the School of Advanced Studies on Language and Society: Mobility, Multilingualism, and Globalization. The interview revolves around the ways he approaches transdisciplinary problems while also attempting to trace a genealogy of concepts like entextualization and communicability. Crafted by him in decades of intellectual and political engagement with indigenous communities and the academia, these concepts are widely spread in anthropology, language studies and public health. This work is licensed under a Creative Commons Attribution 3.0 License.